Productivity Analysis on Liquid Nitrogen (LIN) and Liquid Oxygen (LOX) Production Using Objective Matrix (OMAX) Method - Desi Fitriani; Rahmadhani Nasution; Nurmala Sari (Lembaga Penelitian dan Ilmu Pengetahuan JEPIP, 2023)
The amount of liquid nitrogen (LIN) and liquid oxygen (LOX) production capacity experienced significant fluctuations, so it took several months before it reached the production target implemented by the company. It is necessary to measure productivity on the production floor. This study aims to determine the level of productivity of the production section, and the results of this measurement can be used to evaluate the company's productivity level. Productivity measurement using the Objective Matrix (OMAX) method. The criteria used in this study are material productivity, energy productivity, labor productivity, and finished product productivity. The highest productivity values achieved during measurements from January to December were 900 in LIN production in July and 790 in LOX production in January. Factors that cause low productivity are workers who are less careful or negligent in handling machine damage, the absence of a quality control system in checking raw materials before being placed in the storage warehouse, the lack of a shut-off valve between pipes, causing free air to enter, causing products to be rejected and also machines that work continuously for 24 hours.